Topcoat composition

Through the combination of acrylic polyol resin, polyester resin, nitrofiber resin and pigment, the existing metal coating brightness deterioration and staining problems are solved, and the coating film with high brightness, weather resistance and car wash resistance is achieved, which is suitable for large automotive parts. The complex area of ​​the area improves productivity and economicality.

CN119137227APending Publication Date: 2024-12-13KCC CORP
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202380037619.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-10
Filing Date
2023-04-26
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

Existing metal coatings have brightness degradation and stain problems in achieving luxurious metal texture and large-area complex shape coatings, and are inexpensive in cost and production efficiency, making it difficult to meet the high physical performance needs of automotive parts.

Method used

The topcoat composition using acrylic polyol resin, polyester resin, nitrofiber resin and pigment is used to improve the brightness, weatherability and processability of the coating film by adjusting the molecular weight, hydroxyl value, acid value and glass transition temperature of the resin. .

Benefits of technology

It realizes coatings with high brightness, water resistance, weather resistance and car wash resistance on automotive parts, reduces metal stains and foreign object defects, is suitable for large-area complex shape spraying, and improves production efficiency and economy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005111464750000091
    Figure BDA0005111464750000091
  • Figure BDA0005111464750000092
    Figure BDA0005111464750000092
  • Figure BDA0005111464750000102
    Figure BDA0005111464750000102
Patent Text Reader

Abstract

The invention relates to a finish paint composition. The finish paint composition comprises acrylic polyol resin, polyester resin, nitrocellulose resin and pigment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims the benefit of Korean Patent Application No. 10-2022-0071017 filed on June 10, 2022, in the Korean Intellectual Property Office, the entire contents of which are incorporated herein by reference. Technical Field

[0004] The present invention relates to a base coating composition having excellent metallic texture, which can be sprayed on parts with large areas and complex shapes among automobile parts, such as roof luggage rack rods and skateboards, can achieve a metallic texture appearance, and has excellent physical properties such as adhesion, water resistance, weather resistance and car wash performance. Background Art

[0005] As customers' demands for emotional quality of automobiles increase, automobile manufacturers are using technologies such as coating a metal coating on a substrate or plating or depositing a metal coating to achieve a luxurious metallic texture. At this time, plating or deposition technology has limitations in achieving various colors, and also has limitations in high cost and production volume, and in the process, there is a problem of generating wastewater that causes environmental pollution. In addition, typical metal coatings are low in brightness and metallic texture, and therefore have limitations in achieving a sufficiently luxurious design to meet customers' demands for emotional quality.

[0006] In this regard, Korean Patent No. 10-1843288 (Patent Document 1) discloses a coating composition comprising a topcoat primary color and a transparent body for adjusting the topcoat, wherein the topcoat primary color includes aluminum paste, polyether, cellulose acetate butyrate (CAB) having a molecular weight of 25000 g / mol to 35000 g / mol, polyester resin, polyamide wax, polyolefin wax and solvent. However, there is a problem in the coating composition of the above-mentioned Patent Document 1, that is, it is difficult to achieve a metallic texture due to the deterioration of brightness over time, and stains, etc. may be generated.

[0007] Therefore, there is a need for a coating technology that excels in achieving a metallic texture (compared to typical metal coatings), can achieve a variety of luxurious colors, and achieves economic feasibility and large-scale production. In addition, there is a need for a metallic coating that has excellent various physical properties such as water resistance, weather resistance, high-pressure car wash performance, chip resistance, acid and alkali resistance, and accelerated weather resistance after coating, and can be sprayed on parts with large areas and complex shapes among automotive parts, such as roof rack bars and skateboards. Summary of the invention

[0008] Technical issues

[0009] The present invention provides a topcoat composition which has a better metallic texture than typical metallic paints, realizes a variety of luxurious colors, can be sprayed on parts with large areas and complex shapes among automotive parts, thereby having excellent processability and mass productivity, and has an excellent appearance, especially realizing a metallic texture.

[0010] Technical Solution

[0011] In order to achieve the above object, the present invention provides a topcoat composition comprising an acrylic polyol resin, a polyester resin, a nitrocellulose resin and a pigment.

[0012] Beneficial Effects

[0013] The topcoat composition according to the present invention can be sprayed on a large area of ​​complex shapes, and thus has excellent processability and mass production, which makes the topcoat composition very suitable for coating automotive parts. In addition, the topcoat composition can achieve a variety of luxurious colors and can form a coating film with higher brightness than typical metal coatings.

[0014] In addition, the coating film made of the topcoat composition exhibits excellent physical properties such as water resistance, weather resistance, high-pressure car wash performance, chipping resistance, acid resistance, alkali resistance and accelerated weather resistance. In particular, the coating film made of the topcoat composition has very excellent appearance characteristics due to less occurrence of appearance defects such as metal stains or foreign matter. DETAILED DESCRIPTION

[0015] Hereinafter, the present invention will be described in detail.

[0016] In the present invention, the "number average molecular weight (Mn)" and the "weight average molecular weight (Mw)" may be measured by a method well known in the art, and may be values ​​measured by gel permeation chromatography (GPC).

[0017] In addition, the functional value such as "hydroxyl" can be measured by a method well known in the art, and can be measured by, for example, a titration method and the like.

[0018] The "glass transition temperature" is measured by a typical method known in the art, and can be measured by, for example, the differential scanning calorimetry (DSC) method.

[0019] The topcoat composition of the present invention comprises acrylic polyol resin, polyester resin, nitrocellulose resin and pigment.

[0020] Acrylic polyol resin

[0021] Acrylic polyol resin is the main resin of the coating material containing the resin, and is used to form the coating film and determine the characteristics of the coating film.

[0022] The acrylic polyol resin may be directly synthesized according to a known method, or a commercially available product may be used. At this time, the acrylic polyol resin may be prepared by, for example, polymerizing a hydroxyl-containing acrylic monomer and a vinyl monomer, or polymerizing a hydroxyl-containing acrylic monomer.

[0023] The hydroxyl-containing acrylic monomer may be, for example, a hydroxyalkyl-containing (meth)acrylate, specifically, may include one or more selected from the group consisting of 2-hydroxymethyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 1,3-butylene glycol di(meth)acrylate, 1,4-butylene glycol di(meth)acrylate, ethylene glycol di(meth)acrylate, and 1,6-hexanediol di(meth)acrylate.

[0024] The vinyl monomer may be, for example, a (meth)acrylate substituted or unsubstituted by a hydroxyl group, and specifically may include one or more selected from the group consisting of (meth)acrylic acid, methyl(meth)acrylic acid, methyl(meth)acrylate, ethyl(meth)acrylate, isobutyl(meth)acrylate, n-butyl(meth)acrylate, tert-butyl(meth)acrylate, n-hexyl(meth)acrylate, cyclohexyl(meth)acrylate, 2-ethylhexyl(meth)acrylate, n-octyl(meth)acrylate, isobornyl(meth)acrylate, styrene, methylstyrene, dimethylstyrene, fluorostyrene, ethoxystyrene and methoxystyrene.

[0025] The acrylic polyol resin may be a cellulose acetate butyrate (CAB)-modified acrylic resin. If a cellulose acetate butyrate-modified acrylic resin is used as the acrylic polyol resin, it is modified with cellulose acetate butyrate (which is a polymer), thereby improving the dryness of the coating containing cellulose acetate butyrate, thereby achieving the effect of improving the brightness of the metal topcoat. Cellulose acetate butyrate resin is in a powder form, and therefore, if included alone, the cellulose acetate butyrate resin cannot be sufficiently dissolved in a solvent, which may cause deterioration in the appearance characteristics of the manufactured coating film, such as the formation of irregularities, and therefore it is more preferable to modify the cellulose acetate butyrate resin and include it in the acrylic resin.

[0026] Generally, a coating film formed by applying a coating material dries while the solvent volatilizes, and during this process, the coating film shrinks. As the solvent content increases, the shrinkage rate of the coating film increases, and the force generated during the shrinkage process affects the arrangement of the aluminum pigment, which may increase the brightness. For example, in the case of a polymer resin modified with cellulose acetate butyrate, such as an acrylic polyol resin, the viscosity is high and therefore a large amount of solvent is contained for processability, and a coating film made of a coating material containing the corresponding resin has an effect of improving brightness due to the shrinkage of the coating film when drying.

[0027] Specifically, the acrylic polyol resin may have a cellulose acetate butyrate content of 3 to 15% by weight or 5 to 10% by weight based on the total weight of the resin. If the CAB content is within the above range relative to the total weight of the acrylic polyol resin, there is an effect of improving the spray processability and dryness of the coating composition. In addition, if the content of cellulose acetate butyrate is less than the above range, the molecular weight (Mw) of the acrylic polyol resin decreases, resulting in insufficient effects of improving the dryness and brightness of the coating composition, and if it is greater than the above range, the viscosity increases due to cellulose acetate butyrate, so that there may be problems of reduced solid volume ratio (SVR) of the coating and poor appearance of the manufactured coating film.

[0028] The hydroxyl value (OHv) of the acrylic polyol resin may be 30 mgKOH / g to 80 mgKOH / g, 30 mgKOH / g-60 mgKOH / g, or 40 mgKOH / g to 60 mgKOH / g. If the hydroxyl value of the acrylic polyol resin is within the above range, it has the effect of improving the weather resistance of the manufactured coating film, improving the storage performance of the coating, and the appearance characteristics of the coating film. In addition, if the hydroxyl value of the acrylic polyol resin is less than the above range, the number of sites that react with the isocyanate curing agent is reduced, resulting in a decrease in crosslinking density, which may cause the appearance characteristics, heat resistance, chemical resistance, etc. of the coating film to deteriorate. If it is greater than the above range, the number of sites that react with the isocyanate curing agent is too large, resulting in over-curing, making the coating film brittle, thereby reducing elasticity, and there may be a problem that the storage stability, appearance characteristics and weather resistance of the coating may be reduced.

[0029] In addition, the acid value (Av) of the acrylic polyol resin can be 1 mgKOH / g to 10 mg / g, or 5 mgKOH / g to 10 mgKOH / g. If the acid value of the acrylic polyol tree is within the above range, it has the effect of improving the dispersion stability and storage stability of the coating composition and improving the durability of the coating film. In addition, if the acid value of the acrylic polyol resin is less than the above range, the urethane reaction is accelerated, resulting in accelerated curing reaction, and therefore, there may be problems of shortened storage period and reduced appearance characteristics of the coating film, and if it is greater than the above range, the urethane reaction is excessively delayed, resulting in an extended storage period, thereby there may be problems of slowed drying rate and reduced processability.

[0030] The glass transition temperature (Tg) of the acrylic polyol resin is about 1°C to 20°C, or 1°C to 5°C. If the glass transition temperature of the acrylic polyol resin is within the above range, it has the effect of improving the coating film forming property and anti-foaming property of the composition and the coating film gloss. In addition, if the glass transition temperature of the acrylic polyol resin is lower than the above range, the coating film becomes more flexible, resulting in a decrease in the drying rate of the coating composition, thereby there may be a problem of deterioration in the appearance, anti-sagging and chemical resistance of the coating film, and if it is higher than the above range, there may be a problem that the coating film becomes brittle, thereby reducing the appearance characteristics.

[0031] In addition, the weight average molecular weight (Mw) of the acrylic polyol resin can be 100000 g / mol to 200000 g / mol, or 100000 g / mol to 150000 g / mol. If the weight average molecular weight of the acrylic polyol resin is within the above range, the hardness of the manufactured coating film can be improved. In addition, if the weight average molecular weight of the acrylic polyol resin is less than the above range, the molecular weight of the resin is small, so that the acid resistance and chemical resistance of the manufactured coating film may be reduced. If it is greater than the above range, due to the increase in the molecular weight of the resin, the fluidity and leveling of the coating composition are reduced, so that the appearance of the coating film and the problem of reduced mechanical properties may occur.

[0032] The content of the acrylic polyol resin may be 5% to 15% by weight, or 5% to 12% by weight, based on the total weight of the topcoat composition. If the acrylic polyol resin is included in the above content range, it has the effect of improving the adhesion and impact resistance of the coating film. In addition, if the content of the acrylic polyol resin is less than the above range, the film-forming properties of the coating film may be reduced due to the lack of interface attachment sites, and the adhesion and durability of the coating film may be reduced; if it is greater than the above range, the viscosity of the coating composition may increase due to a large amount of acrylic polyol resin with high viscosity, thereby possibly reducing storage stability.

[0033] Polyester resin

[0034] The polyester resin is an auxiliary resin of the coating composition containing the polyester resin, and prevents metal stains and appearance defects by improving the spreadability and drying of the coating film.

[0035] The polyester resin can be directly synthesized according to known methods, or commercially available products can be used. For example, the polyester resin can be a polymer produced by a condensation reaction between a polyol monomer and a carboxyl-containing monomer. Specifically, the polyester resin can be prepared by a condensation reaction between a polyol monomer and an aliphatic monomer containing a carboxyl group.

[0036] The polyol monomer can be, for example, ethylene glycol, propylene glycol, trimethylolpropane, trimethylolethane, cyclohexanedimethanol, neopentyl glycol, 2-butyl-2-ethyl-1,3-propanediol, 1,4-hexanediol, 1,6-hexanediol, diethylene glycol, dipropylene glycol, triethylene glycol, tripropylene glycol, 1,2-ethanediol, 1,4-butanediol, 1,3-butanediol, 1,5-pentanediol, triethylolpropane, glycerol, pentaerythritol, 3-methylpentanediol, and mixtures thereof.

[0037] In addition, the carboxyl group-containing monomer may be, for example, adipic acid, trimellitic anhydride, terephthalic acid, fumaric acid, phthalic anhydride, hexahydrophthalic anhydride, methylhexahydrophthalic anhydride, tetrahydrophthalic anhydride, methyltetrahydrophthalic anhydride, succinic anhydride, isophthalic acid, azelaic acid, maleic anhydride, and mixtures thereof.

[0038] The number average molecular weight (Mn) of the polyester resin can be 800g / mol to 5000g / mol, or 1000g / mol to 3000g / mol. If the number average molecular weight of the polyester resin is within the above range, a coating film can be stably formed, thereby having the effect of improving the smoothness of the coating. In addition, if the number average molecular weight of the polyester resin is less than the above range, the heat (temperature) required for the urethane reaction is insufficient, and unreacted urethane groups are present, thereby the mechanical properties of the coating film may be reduced, and if it is greater than the above range, the spreadability and dryness of the coating may be reduced.

[0039] In addition, the glass transition temperature (Tg) of the polyester resin may be 0°C or lower, or -30°C to 0°C. If the glass transition temperature of the polyester resin is within the above range, a coating film having excellent coating spreadability and high brightness can be manufactured, and the foreign body feel of the coating film can be reduced by improving the dryness of the coating. On the other hand, if the glass transition temperature of the polyester resin is lower than the above range, there is a problem of insufficient dryness of the coating film, which may lead to insufficient physical properties of the coating film (such as scratches and pencil hardness); if it is higher than the above range, the effect of improving the dryness and spreadability of the manufactured coating film may be insufficient.

[0040] The acid value (Av) of the polyester resin may be 1 mgKOH / g to 30 mgKOH / g, or 1 mg / KOH / g to 10 mg / g. If the acid value of the polyester resin is within the above range, it has the effect of improving the hardness and appearance characteristics of the manufactured coating film. In addition, if the acid value of the polyester resin is outside the above range, the molecular weight of the polyester resin is insufficient, which may result in a decrease in the degree of curing of the coating, thereby preventing the proper formation of the coating film, and there may be a problem of deterioration of the appearance characteristics of the coating film due to insufficient storage performance of the coating.

[0041] In addition, the hydroxyl value (OHv) of the polyester resin may be 100 mg KOH / g to 200 mg KOH / g, or 120 mg KOH / g to 150 mg KOH / g. If the hydroxyl value of the polyester resin is within the above range, it has the effect of improving the durability and chipping resistance of the manufactured coating film, and improving the storage performance and appearance characteristics of the coating. In addition, if the hydroxyl value of the polyester resin is less than the above range, there may be a problem of reducing the durability and chemical resistance of the manufactured coating film due to insufficient crosslinking density, and if it is greater than the above range, there may be a problem of reducing the water resistance, pencil hardness, accelerated weather resistance, etc. of the coating film due to insufficient dryness of the coating composition.

[0042] The content of the polyester resin may be 1% to 20% by weight, or 1% to 10% by weight, based on the total weight of the topcoat composition. If the content of the polyester resin is within the above range, metal stains, paint diffusion, foreign body sensation, etc. are less likely to occur, thereby excellent appearance characteristics and excellent processability of the coating composition. If the content of the polyester resin is less than the above range, foreign body sensation and metal stains of the manufactured coating film may occur. In addition, if the content of the polyester resin is greater than the above range, the brightness of the manufactured coating film may be insufficient.

[0043] In addition, the topcoat composition may include a polyester resin, an acrylic polyol resin and a nitrocellulose resin in a weight ratio of 1:1:5 to 1:4:20. If the weight ratio of the polyester resin, the acrylic polyol resin and the nitrocellulose resin is not within the above range, the brightness of the coating may be reduced and the processability of the coating composition may be deteriorated. For example, when the content of the polyester resin increases and the content of the acrylic polyol resin and the content of the nitrocellulose resin are insufficient, the brightness of the manufactured coating may be reduced. If the content of the polyester and the content of the nitrocellulose resin are insufficient, and the content of the acrylic polyol resin increases, the drying rate of the coating may increase, thereby increasing the stains and foreign body sensation of the coating, and the appearance characteristics may be reduced. If the content of the polyester resin and the content of the acrylic polyol resin are insufficient, and the content of the nitrocellulose resin increases, the coating may have metal stains and may have poor physical properties such as accelerated weather resistance and water resistance.

[0044] Nitrocellulose resin

[0045] Nitrocellulose resin is used to achieve high brightness of the coating film and reduce metal stain defects by improving the orientation of aluminum as a pigment.

[0046] In addition, nitrocellulose resin can be directly synthesized according to known methods, or commercial products can be used. Nitrocellulose resin can be used by mixing powdered nitrocellulose with a solvent such as methyl isobutyl ketone (MIBK), ethanol or toluene. At this time, the nitrocellulose resin can have a nitrocellulose weight of 2% to 10% by weight or 4% to 7% by weight. If the weight of nitrocellulose in the nitrocellulose resin meets the above range, the coating can show high brightness. On the other hand, if the range of nitrocellulose in the nitrocellulose resin is less than the above range, the orientation of aluminum may be reduced, which may cause the brightness of the coating to decrease. If it is greater than the above range, a high molecular weight nitrocellulose resin may be excessively contained, resulting in an increase in the viscosity of the coating, which may cause the coating to dissolve poorly in the solvent.

[0047] The weight average molecular weight (Mw) of the nitrocellulose resin may be 100000 g / mol to 500000 g / mol, or 200000 g / mol to 400000 g / mol. If the weight average molecular weight of the nitrocellulose resin is within the above range, the coating film has increased brightness, excellent appearance characteristics, and excellent coating processability of the coating. In addition, if the weight average molecular weight of the nitrocellulose resin is less than the above range, the brightness of the coating film may be reduced, and if it is greater than the above range, the brightness of the coating film may be insufficient, the coating processability of the coating may be insufficient, and defects such as spots and foreign matter of the coating film, and metal stains may occur.

[0048] In addition, the number average molecular weight (Mn) of the nitrocellulose resin may be 10000 g / mol to 50000 g / mol, or 20000 g / mol to 40000 g / mol. When the number average molecular weight of the nitrocellulose resin is within the above range, a coating having high brightness can be achieved, the appearance characteristics of the coating can be improved, and the coating processability of the coating is excellent. In addition, when the number average molecular weight of the nitrocellulose resin is less than the above range, the brightness value of the coating may be insufficient, and if it is greater than the above range, the brightness value of the coating may be insufficient, the coating processability of the coating may be reduced, and appearance defects such as spots / foreign matter and metal stains may occur.

[0049] The content of the nitrocellulose resin may be 30% to 60% by weight, or 40% to 60% by weight, based on the total weight of the topcoat composition. If the content of the nitrocellulose resin is within the above range, it has the effect of improving the appearance, heat resistance and texture of the manufactured coating film. In addition, when the content of the nitrocellulose resin is less than the above range, there may be a problem of low brightness of the manufactured coating film, and if it is greater than the above range, the spreadability of the coating may be reduced due to excessive nitrocellulose resin.

[0050] pigment

[0051] The pigment is used to give the manufactured coating film a metallic texture and various colors. At this time, the pigment may include, for example, an aluminum-based pigment.

[0052] The aluminum-based pigment may have a cylindrical column or a polygonal column shape. At this time, the height of the aluminum-based pigment may be 10 μm to 150 μm or 20 μm to 100 μm. If the height of the aluminum-based pigment is less than the above range, the weather resistance of the manufactured coating film is insufficient and thus discoloration occurs, and if it is greater than the above range, the brightness of the coating film is insufficient and the metallic feel is insufficient.

[0053] In addition, the average diameter of the aluminum-based pigment may be 1 μm to 15 μm or 6 μm to 10 μm. At this time, if the aluminum-based pigment has a polygonal columnar shape, the average diameter of the bottom may be the average diameter of the circumscribed circle of the bottom polygon. If the average diameter of the aluminum-based pigment is less than the above range, the opacity may be deteriorated, resulting in a problem of the substrate being exposed to the outside, and if it is greater than the above range, there is a problem that it is difficult to achieve a metallic texture.

[0054] The content of the pigment may be appropriately adjusted based on the target color and target opacity of the coating film, for example, the content of the pigment may be 1 to 15 wt %, or 5 to 13 wt %, based on the total weight of the topcoat composition.

[0055] The topcoat composition may also contain a solvent.

[0056] Solvents

[0057] The solvent is used to control the thickness of the coating film and to improve the coating processability of the composition.

[0058] At this moment, solvent can comprise one or more selected from non-polar solvent and polar solvent.Solvent can comprise, for example, be selected from the group consisting of dimethyl glutarate, dimethyl succinate, dimethyl adipate, normal heptane, normal hexane, n-butyl alcohol, toluene, ethyl acetate, n-butyl acetate, isobutyl acetate, 3-methoxybutyl acetate, amyl acetate, ethylene glycol ethyl ether acetate, butanediol acetate, propylene glycol methyl ether acetate, methyl ethyl ketone, methyl isobutyl ketone, acetone, diisobutyl ketone, isophorone and cyclohexanol.Specifically, solvent can comprise one or more selected from the group consisting of n-butyl acetate, dimethyl glutarate, dimethyl succinate, dimethyl adipate and propylene glycol methyl ether acetate.

[0059] In addition, based on the gross weight of the topcoat composition, the content of the solvent may be 5 wt % to 35 wt %, or 7 wt % to 30 wt %. If the content of the solvent is within the above range, the viscosity of the coating composition is suitable, thereby having an excellent processability effect. In addition, if the content of the solvent is less than the above range, there may be a problem of insufficient coating composition viscosity, so insufficient processability, and if greater than the above range, there may be a problem of reduced adhesion of the coating composition or too high viscosity, so insufficient processability.

[0060] The topcoat composition may also contain additives.

[0061] additive

[0062] The additive is not particularly limited as long as it can be generally applied to coatings, but may include, for example, a curing accelerator, a tackifier, a leveling agent, an anti-settling agent, a curing agent, a wax, and the like.

[0063] At this time, the content of the additive may be 1 wt % to 20 wt %, or 3 wt % to 13 wt %, based on the total weight of the topcoat composition.

[0064] The curing accelerator is used to increase the crosslinking density of the coating composition. As the above-mentioned curing accelerator, a curing accelerator commonly used in the coating composition to increase the degree of crosslinking can be used, for example, the curing accelerator can be a metal compound such as dibutyltin dilaurate, dibutyltin diacetate, stannous octoate, dibutyltin mercaptan, tertiary amines such as triethylamine, triethanolamine, 1,4-diazocyclooctane, dimethylethanolamine, ethylmorpholine, dimethylaminoethylmorpholine and dimethylcyclohexylamine, and alkali metal carboxylates or zinc-based complexes. The amount of the curing accelerator used is not particularly limited, and its amount can be adjusted as long as the physical properties of the composition are not affected.

[0065] The tackifier is used to improve the adhesion between the primer film and the clearcoat film, the primer film being the lower end of the topcoat film, and the clearcoat film being the upper end of the topcoat film. As the tackifier, additives commonly used in the coating composition can be used to adjust the interlayer adhesion, and the tackifier can be, for example, a phosphoric acid-modified resin. Specifically, the tackifier can include one or more selected from the group consisting of a phosphoric acid-modified polyester resin and a phosphoric acid-modified epoxy resin.

[0066] The leveling agent is used to impart smoothness to the coating composition to improve the appearance characteristics of the coating film made therefrom, thereby inhibiting the occurrence of orange peel. In addition, the leveling agent can be used without particular limitation as long as it is commonly used in the coating composition, and the leveling agent can be, for example, an ether-modified polysiloxane.

[0067] The anti-settling agent is used to prevent the pigment from settling, thereby improving the storage performance of the coating and improving the appearance characteristics of the manufactured coating film. At this time, the anti-settling agent is not particularly limited as long as it can be used to prevent the pigment in the coating composition from settling, for example, it can be amide wax.

[0068] The topcoat composition may have a viscosity of 25 seconds to 90 seconds, or 28 seconds to 80 seconds at 25°C based on Ford Cup No. 4.

[0069] Additionally, the topcoat composition can include 5 wt % to 25 wt % or 8 wt % to 20 wt % solids, based on the total weight of the composition.

[0070] As mentioned above, topcoat composition according to the present invention can be sprayed on large-area complex shapes, therefore has excellent workability and mass production, which makes topcoat composition very suitable for coating automotive parts. In addition, topcoat composition can realize various luxurious colors, and can form a coating film with higher brightness than typical metal coating. In addition, the coating film made of topcoat composition is excellent in various physical properties such as water resistance, weather resistance, high pressure car wash performance, anti-fragmentation, acid resistance, alkali resistance and accelerated weather resistance. Especially, due to the less occurrence of defects such as metal stains, spots or foreign matter, the coating film made of topcoat composition has very excellent appearance characteristics.

[0071] Mode for Carrying Out the Invention

[0072] Hereinafter, the present invention will be described in more detail with reference to Examples. However, the following Examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention.

[0073] Examples 1 to 18 and Comparative Examples 1 to 4. Preparation of topcoat composition

[0074] The topcoat composition was prepared by mixing the components according to the compositions described in Tables 1 to 4. In Tables 1 to 4, DBE is dibasic ester, PMA is propylene glycol methyl ether acetate, and BA is n-butyl acetate.

[0075] [Table 1]

[0076]

[0077] [Table 2]

[0078]

[0079]

[0080] [Table 3]

[0081] Components (weight %) Embodiment 15 Example 16 Embodiment 17 Embodiment 18 Aluminum-based pigment-1 8 8 8 8 Nitrocellulose resin-1 - - 50 50 Nitrocellulose resin-2 50 - - - Nitrocellulose resin-3 - 50 - - Acrylic polyol resin-1 10 10 10 10 Polyester resin-1 5 5 - - Polyester resin-2 - - 5 - Polyester resin-3 - - - 5 Curing accelerator 1 1 1 1 Solvent-1(DBE) 2 2 2 2 Solvent-2(PMA) 4 4 4 4 Solvent-3(BA) 11 11 11 11 Amide wax 6 6 6 6 Isocyanate 3 3 3 3 Total 100 100 100 100

[0082] [Table 4]

[0083] Components (weight %) Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Aluminum-based pigment-1 8 8 8 8 Nitrocellulose resin-1 55 60 - 50 Acrylic polyol resin-1 10 - 60 - Acrylic polyol resin-4 (unmodified) - - - 10 Polyester resin-1 - 5 5 5 Curing accelerator 1 1 1 1 Solvent-1(DBE) 2 2 2 2 Solvent-2(PMA) 4 4 4 4 Solvent-3(BA) 11 11 11 11 Amide wax 6 6 6 6 Isocyanate 3 3 3 3 Total 100 100 100 100

[0084] The physical properties, manufacturers and product names of the components used in the comparative examples and examples are shown in Table 5.

[0085] [Table 5]

[0086]

[0087]

[0088] Test example: Physical properties evaluation

[0089] Primer (manufacturer: KCC, product name: RP2143 (H) -D / GREY) was applied on the substrate, and then dried naturally for 10 minutes to make a primer film with a thickness of 12 μm. After this, the topcoat composition of the embodiment and the comparative example was applied thereon and dried naturally for 10 minutes to make a topcoat film with a thickness of 5 μm. After this, varnish (manufacturer: KCC, product name: UT5800-A-CLEAR) was applied thereon, and then dried at 80 ℃ for 30 minutes to make a varnish film with a thickness of 30 μm. After this, the physical properties of the final coating were measured by the following method, and the results are shown in Table 6.

[0090] (1) Brightness

[0091] The brightness of the topcoat film was measured by measuring the flop index using an X-RITE MA-98.

[0092] (2) Adhesion

[0093] Adhesion was measured by performing a checkerboard method on the final coating film according to ASTM D3359 tape adhesion test method.

[0094] Specifically, the adhesion is measured by the chessboard method. 100 squares of size (width × length) of 1 mm × 1 mm are made on the surface of the final coating with a knife, and then the squares are removed with tape. At this time, if 100% of the 100 squares remain completely attached, the measured adhesion is evaluated as excellent (◎), if 70% to less than 100% remain attached, it is evaluated as good (○), if 50% to less than 70% remain attached, it is evaluated as average (△), and if less than 50% remain attached, it is evaluated as poor (×).

[0095] (3) Water resistance

[0096] The final coating film was immersed in a constant temperature bath at 40°C for 10 days, and then the adhesion was measured by the checkerboard method in the same manner as in item (2). In this case, the same evaluation criteria were also used.

[0097] (4) Accelerated weathering

[0098] Weather resistance was measured using a CI-5000 device according to ISO 105. At this time, the total amount of irradiation energy was set to 2500 KJ, the irradiation intensity was set to 0.75 W, quartz was used as the inner filter, and S-type borosilicate was used as the outer filter.

[0099] (5) High-pressure car washing performance

[0100] The degree of peeling of the coating film was confirmed by making an X-shaped cross-cut on the final coating with a knife, and then spraying high-pressure water at a pressure of 70 kgf onto the final coating film from a distance of 10 cm using a commercial high-pressure car washer (including a nozzle gun with a gun tip angle of 15°).

[0101] At this time, if there is no peeling coating area, it is evaluated as excellent (◎), if the peeling coating area around the cross-section is less than 3 area % of the total area, it is evaluated as good (○), if the peeling coating area is 3 area % to less than 5 area %, it is evaluated as average (△), and if the peeling coating area is 5 area % or more, it is evaluated as poor (×).

[0102] (6) Processability

[0103] The workability was measured by producing a topcoat film as described above on a test specimen having a size of 30 cm x 30 cm (width x height), and then visually observing the appearance and stains of the coating film surface.

[0104] At this time, if there are no stains, spots or foreign matter, it is evaluated as excellent (◎); if there are slight stains, spots and foreign matter, it is evaluated as good (○); if there are slight stains, spots or foreign matter when observed at a distance of 1 meter, it is evaluated as average (△); if there are obvious stains, spots or foreign matter, it is evaluated as poor (×).

[0105] [Table 6]

[0106]

[0107]

[0108] As confirmed by the results of Table 6 above, the coating films of Examples 1 to 18 of the present invention exhibited overall excellent physical properties in each measurement item.

[0109] On the other hand, Comparative Example 1, in which the polyester resin was not applied, was generally inferior in adhesion, high-pressure car wash performance, and processability. In addition, Comparative Example 2, in which the acrylic resin was not applied, was inferior in brightness, water resistance, accelerated weather resistance, and processability. In addition, Comparative Example 3, in which the nitrocellulose resin was not applied, was generally inferior in brightness, adhesion, water resistance, accelerated weather resistance, high-pressure car wash performance, and processability. In addition, Comparative Example 4, in which the acrylic polyol resin-4 as an unmodified acrylic resin was applied, was inferior in brightness and processability.

Claims

1. A topcoat composition comprising an acrylic polyol resin, a polyester resin, a nitrocellulose resin and a pigment.

2. The topcoat composition according to claim 1, wherein the polyester resin has a number average molecular weight of 800 g / mol to 5000 g / mol, a glass transition temperature of 0°C or less, and an acid value of 1 mgKOH / g to 30 mgKOH / g.

3. The topcoat composition according to claim 1, wherein the acrylic polyol resin is a cellulose acetate butyrate (CAB)-modified acrylic resin having a hydroxyl value of 30 to 80 mgKOH / g, a glass transition temperature of 1 to 20°C, and a weight average molecular weight of 100,000 to 200,000 g / mol.

4. The topcoat composition according to claim 1, wherein the nitrocellulose resin has a weight average molecular weight of 100,000 g / mol to 500,000 g / mol, and a number average molecular weight of 10,000 g / mol to 50,000 g / mol.

5. The topcoat composition according to claim 1, wherein the pigment is in the shape of a cylindrical column or a polygonal column, including an aluminum-based pigment having a height of 10 μm to 150 μm.

6. The topcoat composition according to claim 1, comprising 5 to 15 wt% of an acrylic polyol resin, 1 to 20 wt% of a polyester resin, 30 to 60 wt% of a nitrocellulose resin, and 1 to 15 wt% of a pigment.

Citation Information

Patent Citations

  • Priming coating composition and preparation method thereof

    CN101153155A

  • Coating composition

    CN1817982A

  • Coating compound composition

    JP1988137967A

  • Coating composition and coat finishing method using the same

    JP2006328420A

  • Resin composition and coating body using the same

    JP2014181343A